2016
DOI: 10.1007/s10815-016-0672-x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian kisspeptin expression is related to age and to monocyte chemoattractant protein-1

Abstract: Purpose The objective of this study was to test the hypothesis that ovarian kisspeptin (kiss1) and its receptor (kiss1r) expression are affected by age, obesity, and the age-and obesityrelated chemokine monocyte chemoattractant protein-1 (MCP-1). Methods Ovaries from reproductive-aged and older C57BL/ 6J mice fed normal chow (NC) or high-fat (HF) diet, ovaries from age-matched young MCP-1 knockout and young control mice on NC, and finally, cumulus and mural granulosa cells (GCs) from women who underwent in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 51 publications
0
19
0
3
Order By: Relevance
“…In the present study, GPR54 is expressed in human ECs, monocytes, macrophages, and VSMCs. Ovarian kiss1 and kiss1r expressions are increased in aged mice compared to reproductive‐age mice . Loss of function of GPR54 or KPs induces hypogonadotropic hypogonadism .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, GPR54 is expressed in human ECs, monocytes, macrophages, and VSMCs. Ovarian kiss1 and kiss1r expressions are increased in aged mice compared to reproductive‐age mice . Loss of function of GPR54 or KPs induces hypogonadotropic hypogonadism .…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian kiss1 and kiss1r expressions are increased in aged mice compared to reproductiveage mice. 27 Loss of function of GPR54 or KPs induces hypogonadotropic hypogonadism. 26,28,29 Bowe et al have shown that KPs stimulate the release of insulin from the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Along the same lines, a very recent study confirmed our results demonstrating that ovarian mRNA levels of Kiss1 and its receptor Kiss1R increase in aged mice compared to that in younger mice. Although the authors failed to measure ovarian kisspeptin mRNA in women GCs, they found that ovarian Kiss1R mRNA levels increase according to age (Merhi et al 2016). Interestingly, ovarian KP has a positive correlation with ovarian NE release during the subfertile period in the rat (Fernandois et al 2016).…”
Section: Role Of Ovarian Kisspeptin In Ovarian Ageing and Its Relatiomentioning
confidence: 99%
“…Kisspeptin has been shown to affect ovarian follicular development and ovarian reserve. We have demonstrated that older mice had significantly higher Kiss1 and Kiss1r levels in their ovaries compared with younger mice (39). The sensitivity of kisspeptin may be altered by age-related upregulation of Kiss1r (39).…”
Section: Discussionmentioning
confidence: 73%